Effectiveness of financial support interventions to reduce adverse health outcomes among households in fuel poverty in the United Kingdom - Chithramali Hasanthika Rodrigo; Kusum Singal; Phil Mackie; Shantini Paranjothy (Elsevier, 2024)
Objectives: This systematic review intended to assess the effectiveness of financial support interventions for household fuel poverty in the UK in terms of reducing adverse impacts on the health and wellbeing of recipients. Methods: Bibliographic databases and grey literature sources were searched from the UK for studies that evaluated the health and wellbeing of participants following financial support to optimize indoor heating. Two independent reviewers carried out screening, data extraction and quality assessment of the articles. The outcomes included direct health-related outcomes such as Excess Winter Mortality (EWM), physical/mental health, health services utilization, well-being, and quality of life. Indirect health related outcomes included temperature, condensation/mould/dampness (CMD), fuel efficiency/expenditure and satisfaction with warmth. Due to the heterogeneity of interventions and outcomes, a narrative synthesis of the data was carried out. Results: Twenty studies were included in the review: randomized controlled trials (n = 1), before and after evaluation of interventions (n = 14), ecological studies (n = 1) and modelling studies (n = 4). Sixteen studies assessed impacts of home energy efficiency improvements (HEEI) only, three studies assessed impacts of Winter Fuel Payment (WFP) only while one study assessed impacts of both HEEI and WFP. HEEI studies reported improved indoor temperatures (n = 4), reduced CMD (n = 6), reduced fuel expenditure (n = 4), improved thermal comfort (n = 7), improvements in general health (n = 4), increased wellbeing (n = 4), improved physical health (n = 2), improved mental health (n = 3), reduced new health events (n = 1) and improved existing medical conditions (n = 2). Two HEEI were reported cost effective with added years to life. During modelling studies WFP was found to significantly reduce EWM (n = 2) and fibrinogen levels (n = 1). Conclusions: Most financial support interventions included in this review demonstrated positive impacts on health and wellbeing of recipients supporting their implementation with robust evaluations to better understand the cost effectiveness and long-term impacts in the future. Implementation of these interventions will require cross-sector collaborations, with consideration of which populations are most likely to benefit.